Mulheres nas ciências exatas: condições que possibilitam suas escolhas profissionais - Morales, Andréa Cantarelli (My University, 2022)
This thesis investigated conditions that make possible the professional choices of women who opt for the area of Exact Sciences. Women, invisible in history, already occupy many professional spaces, but the area of Exact Sciences is still predominant in men. The background to this research is a public call project of the CNPq entitled "Girls in the Exact Sciences, Engineering and Computing" in which the University of Caxias do Sul was contemplated. The project benefits five public schools distributed in four municipalities of the Serra Gaúcha. The subjects of this research are five scholarship teacher (one from each school) and four Scientific Initiation scholarship holders who work on this project. The women who make up the corpus of this research are all female professors or students in the area of Exact Sciences. As a methodological procedure, life story interviews and Content Analysis stand out, whose memories sought are based on a specific fact of the life of the interviews, and which contain elements that mediated their professional choice in the area of Exact Sciences. The life history interviews, between the researcher and the research subjects, by video conference, were recorded, transcribed and analyzed. Three major categories emerged from the deconstruction e reconstruction of the corpus: training processes; gender relations and relations with research/project. The category training processes had as subcategories: affective relationships, environment of studies and conditioning of desire. And the gender relations category: educational/professional environment and cultural/generational elements. The analysis was carried out through environment and cultural/generational elements. The analysis was carried out through a dialog, from a hermeneutic perspective interweaving historical and cultural factors of the region of the Serra Gaúcha, together with the experiences of the researcher. The theoretical basis that guided this dialog was subsidized by Heleieth Saffioti on power relations, the concept of gender articulated by Ivone Gebara and the considerations of autonomous and unfinished subject of Paulo Freire. From de analyzes it was observed that many are the questions that permeate the choice of the profession, mainly int the area of Exact Sciences, the first of them being to know the area a with its professions, the relationship with parents, with teachers, financial factors, without leaving aside the gender relations that are latent in this professional area. [resumo fornecido pelo autor]
Esta tese investigou condições que possibilitam as escolhas profissionais das mulheres que optam pela área das Ciências Exatas. A mulher, invisibilizada na história, já ocupa muitos espaços profissionais, mas a área das Ciências Exatas ainda é de predominância masculina. O pano de fundo desta pesquisa é um projeto de chamada pública do CNPq intitulado "Meninas nas Ciências Exatas, Engenharias e Computação" com o qual a Universidade de Caxias do Sul foi contemplada. O projeto beneficia cinco escolas públicas distribuídas em quatro municípios da Serra Gaúcha. Os sujeitos desta pesquisa são cinco professoras bolsistas (uma de cada escola) e quatro bolsistas de Iniciação Científica que atuam neste projeto. As mulheres que compõem o corpus desta pesquisa são todas professoras ou alunas da área das Ciências Exatas. Como procedimento metodológico destaca-se as entrevistas de histórias de vida e a Análise de Conteúdo, cujas memórias buscadas estejam baseadas em um fato específico da vida das entrevistas, e que contenham elementos que mediaram sua escolha profissional na área das Ciências Exatas. As entrevistas de história de vida, entre a pesquisadora e os sujeitos da pesquisa, por videoconferência, foram gravadas, transcritas e analisadas. Da desconstrução e reconstrução do corpus emergiram três grandes categorias: processos formativos; relações de gênero e relações com a pesquisa/projeto. A categoria processos formativos teve como subcategorias: relações afetivas, ambiente de estudos e condicionamento do desejo. E a categoria relações de gênero: ambiente educacional/profissional e elementos culturais/geracionais. A análise foi realizada através de um diálogo, numa perspectiva hermenêutica entrelaçando fatores históricos e culturais da região da Serra Gaúcha, juntamente com as vivências da pesquisadora. A base teórica que norteou este diálogo foi subsidiada por Heleieth Saffioti sobre as relações de poder, o conceito de gênero articulado por Ivone Gebara e as considerações de sujeito autônomo e inacabado de Paulo Freire. Das análises observou-se que muitas são as questões que permeiam a escolha da profissão, principalmente na área das Ciências Exatas, sendo a primeira delas conhecer a área com suas profissões, a relação com os pais, com os professores, os fatores financeiros, sem deixar de lado as relações de gênero que se encontram latentes nessa área profissional. [resumo fornecido pelo autor]
Keywords: Profissões - Mulheres; Mulheres - Orientação profissional; Professions - Women; Women - Vocational guidance